Preservação digital e os periódicos científicos eletrônicos brasileiros em Ciência da Informação - Araujo, Priscilla Mara Bermudes (2015)
Discusses about the digital preservation of electronic journals in Information Science published in Brazil. Emphasizes first, concepts and functions related to electronic journals and digital objects, as well as procedural elements and practices involved in the framework of digital preservation of electronic journal, according to the specialized literature. International and Brazilian initiatives actions were also identified, among them, Cariniana Network, a pioneering Brazilian collective initiative of digital preservation. Then, analyzes the results of the questionnaire applied to the selected journals for this research and observation in sites The Keepers and Cariniana Network to complement the empirical research inherent in digital preservation of these journals. Based on this theoretical and analytical contribution it was possible to present an overview of digital preservation practices of Brazilian electronic journals in information science, emphasizing the importance of digital preservation actions to ensure proper storage, usability and long-term access to these digital objects.